FORMATION OF MOTIVATION TO RESEARCH ACTIVITIES OF FUTURE TEACHERS - Baizhanova, S.A.; Balgabayeva, G.Z.; Lee, E.D. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
Motivation as the driving force of human behavior takes the leading place in the structure of personality. Motivation to research activities of future teachers - is a stimulation to creative activity, the process of awakening yourself and others to research work, impact on human behavior to achieve personal, collective and social goals. The model of formation of motivation to research activities of future teachers contains the main components: motivational-target, cognitive, operational-effective, evaluation. The motivational sphere includes positive motivation to the teacher's profession, awareness of the creative nature of professional activity, improvement of pedagogical skills, aspiration and readiness for self-improvement.
Keywords: motivation; research activity; future teachers; creativity; experimental work; professional activity; efficiency